Bivariate Analysis of Factors Related to Medication Adherence in Tuberculosis Patients - Daa Husaeni; Cecep Heriana; Fitri Kurnia Rahim; Lely Wahyuniar (Jurnal Medisci, 2026)
Background. Tuberculosis (TB) is still a major public health problem in Indonesia, with a significant trend of increasing cases in recent years. The success of TB treatment is highly dependent on the patient's compliance in taking Anti-Tuberculosis Drugs (OAT) regularly and completely. Purpose. This study aims to analyze factors related to medication adherence to tuberculosis patients in the working area of the Darma Health Center, Kuningan Regency. Method. This study uses an observational analytical design with a bivariate approach. The sampling technique used a total sampling of 90 TB patients. Data was collected using standardized questionnaires that had been tested for validity and reliability, then analyzed using Chi-Square and Odds Ratio (OR) tests. Results. The results showed that family support, access to health facilities, attitudes, and knowledge levels had a significant relationship with medication adherence (p < 0.05). Lack of family support increased the risk of non-compliance by 6.7 times, difficult access to health facilities increased the risk by 7.1 times, less positive attitudes by 5.9 times, and lack of knowledge by 11 times. Meanwhile, the role of health workers and motivation did not show a significant relationship with medication adherence. Conclusion. The conclusions of this study confirm that social, behavioral, and cognitive factors have an important role in determining TB treatment adherence. Implementation. TB control interventions need to focus on improving patient education, strengthening family support, and improving access to health services to increase the success of tuberculosis treatment.